2022
DOI: 10.1002/cctc.202201004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Degree of Nitridation of Ta2O5 to TaON Particles and their Photocatalytic Oxygen Evolution Properties

Abstract: Oxynitride or nitride photocatalysts are typically synthesized by heating oxide precursor particles at high temperatures under NH3 flow. Although there are numerous reports on optimizing the nitridation conditions for different materials, the detailed nitridation mechanism is still unclear. In this study, the nitridation of Ta2O5 to TaON was investigated. The degree of nitridation was quantitatively analyzed using the change in the weight of a powder after nitridation. Three regions were identified in the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The optimum flow rate was 20 mL min –1 , indicating that one-fifth of the flow rate occurred during the STON synthesis. It has been reported that the flow rate and nitridation time are both linearly proportional to the degree of nitridation in TaON . Therefore, higher flow rates may have caused overnitridation, resulting in a reduced activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum flow rate was 20 mL min –1 , indicating that one-fifth of the flow rate occurred during the STON synthesis. It has been reported that the flow rate and nitridation time are both linearly proportional to the degree of nitridation in TaON . Therefore, higher flow rates may have caused overnitridation, resulting in a reduced activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the flow rate and nitridation time are both linearly proportional to the degree of nitridation in TaON. 13 Therefore, higher flow rates may have caused overnitridation, resulting in a reduced activity. The loading amount was also optimized to 0.3 wt % (Ir base), although the activity did not significantly change in the range of the investigated conditions, whereas the STON particles without the cocatalyst produced only a negligible amount of oxygen.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[11] First, thermal ammonolysis requires high temperature and involves multiple diffusion steps. [12] Second, the partial decomposition of ammonia gas into hydrogen and nitrogen at high temperatures may cause Scheme 1. Schematic of metallic-powder-assisted nitridation route used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] First, thermal ammonolysis requires high temperature and involves multiple diffusion steps. [ 12 ] Second, the partial decomposition of ammonia gas into hydrogen and nitrogen at high temperatures may cause undesired side reactions. [ 13 ] Third, the exchange kinetics of reactive nitrogen species with the lattice oxygen of the oxide precursor is usually sluggish, which generally leads to weak or limited nitrogen substitution for oxygen atoms and causes nitridation to occur only on the surface of the sample.…”
Section: Introductionmentioning
confidence: 99%